Озорные рассказы о школьниках - Данкова Р. (Библиотека младшего школьника, 2011)
Экземпляры: ФО- 1; 10; (20110303) / Инвентарный номер: 46724 / Цена: 80.60 / Сис.шифр: 84(2Рос=Рус)6 46724 / Авт.знак: О-47 / ББК: 84(2Рос=Рус)6